Suggested Cut-Off Values for Vitamin D as a Risk Marker for Total and Cardiac Death in Patients with Suspected Acute Coronary Syndrome - Naesgaard, Patrycja A. (2016)
Background: Several studies have demonstrated an association between low vitamin D levels and cardiovascular risk. Vitamin D cut-off levels are still under debate.Objectives: To assess two cut-off levels, 40 and 70 nmol/L, respectively, for vitamin D measured as 25-hydroxyvitamin D in chest pain patients with suspected acute coronary syndrome.Methods: We investigated 1853 patients from coastal-Norway and inland NorthernArgentina. A similar database was used for pooling of data. Two-year follow-up data including all-cause mortality, cardiac death, and sudden cardiac death in the total patient population were analyzed, applying univariate and multivariable analysis.Results: Two hundred fifty-five patients with known vitamin D concentrations died. In the multivariable analysis, there was a decrease in total mortality above a cut-off level of 40 nmol/L and a decrease in cardiac death above a cut-off level of 70 nmol/L [HRs of 0.66 (95% CI, 0.50?0.88), p = 0.004 and 0.46 (95% CI, 0.22?0.94), p = 0.034, respectively].Conclusion: Vitamin D cut-off levels of 40 and 70 nmol/L were related to total mortality and cardiac death, respectively.